2015
DOI: 10.1007/3418_2015_114
|View full text |Cite
|
Sign up to set email alerts
|

New Chemistry with Anionic NNN Pincer Ligands

Abstract: The use of tridentate anionic pincer ligands in organometallic chemistry has gained considerable importance, particularly in the field of homogenous catalysis. This chapter focuses on the recent developments of anionic tridentate NNN pincer ligands from their synthesis to coordination chemistry and their applications in forming stable transition metal complexes for applications in catalytic transformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 124 publications
(135 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, various other reactions can also be catalyzed with the in situ formed bis­(oxazolinyl)­carbazolide chromium complex, including among others the selective functionalization of halide-substituted olefins with aldehydes or ketones, respectively, yielding the corresponding secondary or tertiary alcohols, with high enantioselectivities. Access to targeted compounds with excellent selectivity renders this chromium-catalyzed protocol with high relevance, justifying the segments in various reviews regarding the use of the bis­(oxazolinyl)­carbazole ligand in the Nozaki-Hiyama reaction. ,,,,,, Hence, the topic will only be highlighted in this communication with the inclusion of selected examples illustrating the synthetic potential of the catalytic reaction when catalyzed with the in situ formed bis­(oxazolinyl)­carbazolide chromium complex.…”
Section: Wingtip Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, various other reactions can also be catalyzed with the in situ formed bis­(oxazolinyl)­carbazolide chromium complex, including among others the selective functionalization of halide-substituted olefins with aldehydes or ketones, respectively, yielding the corresponding secondary or tertiary alcohols, with high enantioselectivities. Access to targeted compounds with excellent selectivity renders this chromium-catalyzed protocol with high relevance, justifying the segments in various reviews regarding the use of the bis­(oxazolinyl)­carbazole ligand in the Nozaki-Hiyama reaction. ,,,,,, Hence, the topic will only be highlighted in this communication with the inclusion of selected examples illustrating the synthetic potential of the catalytic reaction when catalyzed with the in situ formed bis­(oxazolinyl)­carbazolide chromium complex.…”
Section: Wingtip Effectsmentioning
confidence: 99%
“…Access to targeted compounds with excellent selectivity renders this chromium-catalyzed protocol with high relevance, justifying the segments in various reviews regarding the use of the bis(oxazolinyl)carbazole ligand in the Nozaki-Hiyama reaction. 99,100,305,307,308,319,320 Hence, the topic will only be highlighted in this communication with the inclusion of selected examples illustrating the synthetic potential of the catalytic reaction when catalyzed with the in situ formed bis(oxazolinyl)carbazolide chromium complex. In a continuation of the work by Furstner et al, 321,322 Nakada and co-workers sought to decrease the stoichiometric use of chromium in the Nozaki-Hiyama C−C bond-forming reaction to catalytic amounts.…”
Section: Introducing Chiral Peripheries At the Wingtip Positionsmentioning
confidence: 99%
“…■ T-SHAPED NICKEL COMPLEXES STABILIZED BY NNN PINCER LIGANDS Apart from the PNP ligands discussed above, pincer ligands with three nitrogen-based donors (i.e., NNN pincer ligands) have been widely used in coordination chemistry and catalysis. 50 The use of chiral oxazoline units at the "wingtip" position of a pincer ligand has proven especially successful in asymmetric catalysis. 51 We have recently shown that the nickel(II) chlorido complex 15 bearing a pmbox ligand can isomerize to the iso-pmbox complex 16, which is then reacted with lithium triethylborohydride to give the corresponding nickel(II) hydride 17.…”
Section: ■ Monovalent T-shaped Complexes Stabilized By Amidophosphine...mentioning
confidence: 99%
“…Apart from the PNP ligands discussed above, pincer ligands with three nitrogen-based donors (i.e., NNN pincer ligands) have been widely used in coordination chemistry and catalysis . The use of chiral oxazoline units at the “wingtip” position of a pincer ligand has proven especially successful in asymmetric catalysis …”
Section: T-shaped Nickel Complexes Stabilized By Nnn Pincer Ligandsmentioning
confidence: 99%